(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2001)
If Max Brod had not published Kafka’s manuscripts, it would have been a huge loss for world literature. If Antón Arrufat had respected the intention of his friend Piñera and had not published poems that the poet had not intended for the public, Piñera and his readers would have won (Review)